Antibiotic treatment for 7 days versus 14 days in patients with uncomplicated bloodstream infections: a Systematic review and meta-analysis of randomized controlled trials and trial sequential analysis - Zhao, Changyun; Chen, Changqin; Lu, Difan; Cai, Kailun; Hu, Weihang; Mao, Wenchao (Frontiers in Medicine, 2025)
BackgroundThe optimal duration of antibiotic therapy for bloodstream infections (BSI) remains a topic of ongoing debate. To address this, we conducted a meta-analysis to evaluate the efficacy and safety of 7-day and 14-day antibiotic regimens in the treatment of BSI.MethodsWe performed a comprehensive search of PubMed, Web of Science, Embase, and the Cochrane Library from the inception of these databases up to March 10th, 2025. Randomized controlled trials (RCTs) comparing 7-day and 14-day antibiotic regimens for the treatment of BSI will be included. The Cochrane risk of bias assessment tool was used to evaluate the risk of bias. The primary outcomes were all-cause mortality, 90-day mortality, while secondary outcomes included relapsed bacteremia, readmissions or prolongation of hospitalization, suppurative complications, emergence of resistance, length of stay in hospital, and adverse events. Trial sequential analysis (TSA) was then conducted.ResultsThe meta-analysis included four RCTs involving 4,794 patients. The results indicated no statistically significant differences between the 7-day and 14-day antibiotic regimens in terms of all-cause mortality (RR = 0.96, 95% CI: 0.73–1.25, p = 0.75) or 90-day mortality (RR = 0.94, 95% CI: 0.80–1.10, p = 0.45). When the analysis was restricted to BSI caused by Gram-negative bacteria (GNB), no statistically significant differences were observed in all-cause mortality or 90-day mortality. The 7-day antibiotic regimen was associated with a significantly shorter length of stay in hospital compared to the 14-day regimen. However, no significant differences were observed in other secondary outcomes or adverse events, including acute kidney injury (AKI), Clostridioides difficile infection (CDI), diarrhea, and rash. And the TSA suggested that the current findings may have yielded a false negative conclusion.ConclusionFor BSI, the 7-day antibiotic regimen was associated with a significantly shorter length of stay in hospital compared to the 14-day regimen, while demonstrated comparable efficacy and safety outcomes. From this perspective, a 7-day antibiotic regimen seems to be more advisable. However, it is imperative to conduct additional large-scale RCTs to validate and substantiate our findings.Systematic review registrationRegistration ID: CRD42024617359; https://www.crd.york.ac.uk/PROSPERO/view/CRD42024617359.